Man Surgeon Treating Women in Ibnu Sina Teaching Hospital: Issue & Challenges - B E, Hasbi; D, Ikram; S D, Pramono (International Journal of Human and Health Sciences (IJHHS), 2024)
Objectives: A doctor is generally able to provide medical assistance to both male and female patients. In Islam, as long as this is for the sake of healing the patient, touching women is permissible. However, in reality, female patients who are examined by male doctors still feel awkward. In addition, patient openness is sometimes not fully to the doctor. The Ibn Sina Teaching Hospital is a public hospital that has an Islamic philosophy and most surgeons are male while there are more female patients with their own challenges. Methods: This is a qualitative study that collects patient data through interviews in 2023. The patients are all female patients with male surgeons. Interviews were conducted regarding the challenges and feelings of patients being treated and examined by male surgeons both in outpatient and inpatient care. Results: A total of 16 female patients were examined. Most patients feel that the inpatient surgeon's service is quite good and they get excellent surgical services. In addition, during preparation, surgery and post-surgery, patients receive good surgical services. However, on an outpatient basis, the doctor provides services and explains the disease in a simple and fast manner. For surgeons, serving both male and female patients is the same. However, female patients require a slightly longer interview time because the explanation must also be conveyed to the husband as the decision maker. Conclusion: The service of female patients by male surgeons is considered quite good. Most of the patients experienced no problems when examined by male surgeons. In contrast to outpatient services, patients get sufficient and concise information. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S58